2008
DOI: 10.3382/ps.2007-00039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Storage Conditions and Shotshell Wounding on the Hygienic Condition of Hunted, Uneviscerated Pheasant (Phasianus colchicus)

Abstract: The effects of shot wounds on the hygienic conditions of pheasants (particularly those in the body cavity) were studied. Slaughtered (n = 33) and hunted pheasants (31 specimens with, and 33 specimens without shots in the body cavity) were stored uneviscerated at 0 and 4 degrees C. Specimens were taken at d 0, 3, 7, and 14. Hunted pheasants differed from slaughtered pheasants with respect to muscular hemorrhages and blood and fecal matter in the body cavity but also with regard to the presence of Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 8 publications
5
16
0
Order By: Relevance
“…This is in agreement with data reported by Paulsen et al (2008), who also found very low concentrations of biogenic amines in pheasants stored for 14 days at temperatures of 0 °C and 4 °C (in 90% of samples, biogenic amine concentrations did not exceed the 1 mg/kg limit). Low concentrations of biogenic amines were ascribed to low incidence of contaminating microorganisms (Paulsen et al 2008). Based on our results, we may conclude that uneviscerated pheasants killed by pithing can be stored, as far as biogenic amines are concerned, for up to 21 days at temperatures from 0 to 7 °C.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with data reported by Paulsen et al (2008), who also found very low concentrations of biogenic amines in pheasants stored for 14 days at temperatures of 0 °C and 4 °C (in 90% of samples, biogenic amine concentrations did not exceed the 1 mg/kg limit). Low concentrations of biogenic amines were ascribed to low incidence of contaminating microorganisms (Paulsen et al 2008). Based on our results, we may conclude that uneviscerated pheasants killed by pithing can be stored, as far as biogenic amines are concerned, for up to 21 days at temperatures from 0 to 7 °C.…”
Section: Discussionsupporting
confidence: 93%
“…In view of game bird microbial contamination and temperature variables during hanging, we might assume a deterioration of hygienic quality of the game and an associated marked increase in biogenic amine content in the meat of game birds. Paulsen et al (2008) looked into the issue of biogenic amines in uneviscerated pheasants. Raising pheasants for slaughter and the subsequent meat production has recently acquired great importance (Hofbauer et al 2010).…”
mentioning
confidence: 99%
“…The effect of temperature on the formation of biogenic amines was described by Naila et al (2011). Paulsen et al (2008) Table 2. Concentrations of selected biogenic amines in thigh muscle of drawn pheasants killed by pithing stored at ±7 °C.…”
Section: Discussionmentioning
confidence: 99%
“…This particularly applies to gamebirds where the method of killing is the factor causing the greatest concern regarding safety. Shotgun shells may damage the intestinal cavity resulting in microbial contamination of the meat; Paulsen et al (2008) investigated the effect of shotshell wounding on hunted, uneviscerated Pheasant and found a loss of hygienic quality only at day 7 (stored at 0-4°C) caused by the presence of Escherichia coli (>1 log 10 cfu/g). Alternatively, emphasis can also be placed on disposing gamebird carcasses where gunshot damage to the intestinal cavity has occurred so as to ensure that contaminated meat is not consumed.…”
Section: Safetymentioning
confidence: 99%